2022
DOI: 10.1140/epjc/s10052-021-09917-9
|View full text |Cite
|
Sign up to set email alerts
|

Closing the window on WIMP Dark Matter

Abstract: We study scenarios where Dark Matter is a weakly interacting particle (WIMP) embedded in an ElectroWeak multiplet. In particular, we consider real SU(2) representations with zero hypercharge, that automatically avoid direct detection constraints from tree-level Z-exchange. We compute for the first time all the calculable thermal masses for scalar and fermionic WIMPs, including Sommerfeld enhancement and bound states formation at leading order in gauge boson exchange and emission. WIMP masses of few hundred TeV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 84 publications
4
128
0
Order By: Relevance
“…The formation of metastable bound states and their subsequent decays into radiation open new annihilation channels for DM that can significantly reduce its predicted relic density [3]. Besides being supported by unitarity arguments, the emergence of this type of inelasticity in the multi-TeV regime has been shown by explicit calculations in a variety of theories [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition to DM freeze-out, its implications extend to DM indirect detection and collider signatures, as discussed in the original works of ref.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The formation of metastable bound states and their subsequent decays into radiation open new annihilation channels for DM that can significantly reduce its predicted relic density [3]. Besides being supported by unitarity arguments, the emergence of this type of inelasticity in the multi-TeV regime has been shown by explicit calculations in a variety of theories [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In addition to DM freeze-out, its implications extend to DM indirect detection and collider signatures, as discussed in the original works of ref.…”
Section: Introductionmentioning
confidence: 91%
“…The reason has been two-fold: the capture into the ground state is indeed dominant in some models [51][52][53], while excited states tend to decay into radiation more slowly and be ionised rapidly until lower temperatures than the ground state, when the DM density is smaller, which limits their efficacy in depleting the DM abundance. However, recent studies have shown that this does not hold in general; capture into excited states can be faster than into the ground state, while de-excitations increase (decrease) the effective decay (ionisation) rate of the excited states [15,[19][20][21]. Considering excited levels is hence crucial for predicting the DM density accurately [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…where K 1 is the first modified Bessel function of second kind and s ≡ (p e − + p e + ) 2 is the electron positron invariant mass squared. The solution of the Boltzmann equation in (11) can be obtained by integrating the temperature T from neutrino decoupling T max ≈ 1 MeV,…”
Section: A Boltzmann Equation and Its Solutionmentioning
confidence: 99%
“…With typical experimental threshold at O(1) keV, direct detection experiments are only sensitive to the DM mass above GeV. In the GeV∼TeV mass range, the null result from the direct detection experiments has put very strong limit on the DM interaction strength with the Standard Model (SM) particles [10,11]. In contrast, the cross section of sub-GeV light DM scattering with SM particles is much less stringently constrained and can still be large [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, they will be limited by radon backgrounds rather than the irreducible neutrino flux from solar, atmospheric and diffuse cosmic sources [3,4]. Whatever the experimental outcome -improved exclusion limits, a few tantalizing events, or a dark matter signal detection -there will be strong motivation to reach the irreducible neutrino detection limit [5]. Removing radon-related backgrounds would result in an experiment with neutrinos as the dominant background.…”
Section: Introductionmentioning
confidence: 99%